THE INVENTION OF CASTE WARFARE IN YUCATÁN, 1847-1927 (Tzintzun, Revista de Estudios Históricos, 2022)
The indigenous rebellion that broke out in Yucatan in July 1847 deeply shookthe regional society and detonated intellectual activities with the aim of imposinga vision of the events. The aim of the essay is to unravel the invention of theneologism Caste War, built by different artificers, from historians, journalists,literary or writers in a long period, from the detonation of the internal war conflictuntil the development of an ultramontane discourse in 1927.
Keywords: Caste War; Social War; ideology; invention; Yucatan